Study of strength and toughness in Japanese sword produced from Tamahagane steel by Tatara process. (18th January 2012) - Yaso, M.; Takaiwa, T.; Minagi, Y.; Kanaizumi, T.; Kubota, K.; Noda, Y.; Das, Ananda Kumar; Morito, S.; Ohba, T.
Several metallurgical properties of a traditional Japanese sword were investigated from sharp edge to core area in cross-section and on surface. The microstructure is found to be lath martensite at the sharp edge and the prior austenite grain size is observed to be very fine. Towards the inside from the sharp edge in the cross-section, the microstructure changes gradually from hard martensite to soft ferrite. Micro hardness along the centre line in the crosssection was measured. The sharp edge is very hard and the hardness decreases drastically with the detachment from the sharp edge. The hardness gradient on the hardness distribution curve, tan θ is defined here. The value of tan θ is estimated as an important factor for the explanation of mechanical properties of Japanese swords. Furthermore, residual stress was measured with XRD. Large compressive stress is consequently found on the surface including the sharp edge, which is effective for strengthening the Japanese sword.